Research agenda for ending preventable maternal deaths from postpartum haemorrhage: a WHO research prioritisation exercise - Fernando Althabe; Olufemi T Oladapo; Arri Coomarasamy; A Metin Gülmezoglu; Mariana Widmer; Ioannis D Gallos; Caitlin R Williams; Guervan Adnet; Md Asiful Islam; Sara Rushwan (BMJ Global Health)
Introduction Postpartum haemorrhage (PPH) remains the leading cause of maternal death. Yet there is a lack of clarity around what research is needed to determine what works and how best to deliver proven PPH interventions. This article describes a WHO-led effort to develop a global PPH research agenda for 2023–2030, to reinvigorate research and innovation while avoiding duplication and waste.Methods Potential questions were culled from evidence gaps in a forthcoming Lancet PPH series, a pipeline analysis on PPH medicines and devices, international PPH guidelines, previous research prioritisation efforts and submissions from a reference group of PPH experts and stakeholders. Questions were deduplicated and consolidated, categorised into three tracks (innovation, implementation and cross-cutting) and subjected to an online prioritisation survey. Survey participants (n=120) assessed these questions using five criteria (answerability, effectiveness, deliverability, maximum potential for disease burden reduction and equity) following the Child Health and Nutrition Research Initiative methodology. The outcome of this exercise was complemented by an in-person consensus meeting (Global PPH Summit from 7 March 2023 to 10 March 2023 in Dubai, United Arab Emirates) to finalise the research agenda.Results Fifteen research questions (five per track) were identified as top priority. The top question per track called for research on the comparative effectiveness and safety of alternative routes of administration (other than the intravenous route) of tranexamic acid in the treatment of PPH (innovation); identifying barriers and facilitators affecting the adoption and use of evidence-based recommendations for PPH management (implementation) and the effectiveness of a strategy of early detection and first response treatment using a bundle of recommended interventions for improving PPH-related outcomes (cross-cutting).Conclusion This shared research agenda should guide future investments into PPH studies with high potential to transform policy and clinical practice in the near term to medium term. Funding for the new research priorities is urgently needed.